Effect of Differences Growing Media and Controlled Release Fertilizer Dosages On The Growth Of Aglaonema - Adi Noor Prayogi; Emi Yunida; Bela Ayu Pratiwi (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: This study aims to determine the effect of planting media composition and fertilizer dosage. Controlled Release Fertilizer (CRF) on the growth of Aglaonema 'Dud Unyamanee' as an effort to increase fertilization efficiency. Methodology: The experiment was conducted in greenhouse using a factorial Completely Randomized Design (CRD). The first factor is the planting medium (husk, husk + burnt husk, husk + cocopeat) and the second factor was the CRF dose (0 g and 2 g per plant). Observations were made on vegetative growth variables 10 weeks after planting. Results: Data analysis showed that 2 g CRF application significantly increased the number of leaves, leaf area, number of roots, root length, and stem diameter compared to the control. There was a significant interaction between the growing medium and CRF dose. Findings: Combination of rice husk media +cocopeatwith a CRF dose of 2 gr (M3D1) it was proven to produce the best growth in all observation variables. Novelty: This research applies the technology of slow release fertilizer (CRF) which has not been widely explored in Aglaonema cultivation to overcome the problem of inefficiency of conventional fertilizers. Originality: This study offers specific solutions for the use of media-based cocopeat which is combined with CRF to optimize nutrient absorption and reduce the environmental impact on potted ornamental plants. Conclusion: The use of mixed media of husk and cocopeat accompanied by the application of 2 grams of CRF is highly recommended to stimulate optimal growth of Aglaonema. Paper Type: Research Articles.